KEADILAN RESTORATIF DALAM PEMBINAAN ANAK YANG MELAKUKAN TINDAK PIDANA TERORISME - RENY REBEKA MASU, 031227017330 (2019)
The title of this desertation is “Restorative Justice in Developing Child Who Commit Terrorism Crime”. The commitment of Indonesia nation to give protection to children is seen in law No 11, 2012 about Children Criminal Justice System (UU SPPA), which obliged every phase of SPPA to prioritize Restorative Justice approach, however, restorative justice concept becomes obscure in the development phase in Special Correctional Institution for Children (LPKA) and it is not recognized in law No12, 1995 about Correctional Institution. The obscurity and the absence of restorative justice concept in the development phase impact the children who commit terrorism which are categorized as serious criminal act by the law of SPPA, and they do not get restorative justice through diversion in the resolution process, they only get it in the phase of development in LPKA. The problem formulation is being focused on: 1. Philosophy of children development who commit terrorism criminal act based on restorative justice approach; 2. Development concept formulation of Children who commit terrorism based on restorative justice approach in Correctional Institution System. The research type is normative research which applying law approach (statute approach), conceptual approach and case approach. To solve philosophy problem above it takes development concept reformulation based on restorative justice in law of SPPA and in law of Correctional Institution to give protection to the children who commit terrorism criminal act that are also as victims; Building development mechanism outside LPKA that involves perpetrator and victim and also all related parties for recovery purpose. In order to do that, it needs capacity building of Cross-Cultural Education Institution that specialize to be development recommendation for child who commit terrorism crime based on restorative justice that specially stand as LPKA institution